Laser Metal Deposition Process of Metals, Alloys, and Composite Materials - Mahamood, Rasheedat Modupe (Engineering Materials and Processes,, 2018)
This book highlights the industrial potential and explains the physics behind laser metal deposition (LMD) technology. It describes the laser metal deposition (LMD) process with the help of numerous diagrams and photographs of real-world process situations, ranging from the fabrication of parts to the repair of existing products, and includes case studies from current research in this field. Consumer demand is moving away from standardized products to customized ones, and to remain competitive manufacturers require manufacturing processes that are flexible and able to meet consumer demand at low cost and on schedule. Laser metal deposition (LMD) is a promising alternative manufacturing process in this context. This book enables researchers and professionals in industry gain a better understanding of the LMD process, which they can then use in real-world applications. It also helps spur on further innovations.